2020
DOI: 10.1002/path.5457
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the molecular classification of pediatric brain tumors: a guide to the galaxy

Abstract: Central nervous system (CNS) tumors are the most common solid tumor in pediatrics, accounting for approximately 25% of all childhood cancers, and the second most common pediatric malignancy after leukemia. CNS tumors can be associated with significant morbidity, even those classified as low grade. Mortality from CNS tumors is disproportionately high compared to other childhood malignancies, although surgery, radiation, and chemotherapy have improved outcomes in these patients over the last few decades. Current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 121 publications
(150 reference statements)
0
51
0
4
Order By: Relevance
“…All analyses conducted so far have focussed on glioblastoma in adults, but glioblastoma also occurs in the paediatric population. In addition, children are affected by several other forms of glioma which are rare in the adult population 47 . Analysis of two published microarray datasets (http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE50161 48 and http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE50021 49 ) revealed that FAP gene expression was above normal brain levels in a variable proportion of tumor tissues for five distinct paediatric glioma types (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All analyses conducted so far have focussed on glioblastoma in adults, but glioblastoma also occurs in the paediatric population. In addition, children are affected by several other forms of glioma which are rare in the adult population 47 . Analysis of two published microarray datasets (http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE50161 48 and http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE50021 49 ) revealed that FAP gene expression was above normal brain levels in a variable proportion of tumor tissues for five distinct paediatric glioma types (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, children are affected by several other forms of glioma which are rare in the adult population. 47 Analysis of two published microarray datasets (GSE50161 48 and GSE50021 49 ) revealed that FAP gene expression was above normal brain levels in a variable proportion of tumor tissues for five distinct paediatric glioma types (Figure 7). For paediatric glioblastoma, the proportion of FAPexpressing tumors (32.4%) was comparable to the adult disease, while pilocytic astrocytoma, a lower grade glioma, was characterised by a lower frequency of FAP-expressing tumors (13.3%), again similar to adult low-grade glioma.…”
Section: High-parameter Flow Cytometry Confirms Cell Surface Expressimentioning
confidence: 99%
“…The incidence of CNS tumors in children and adolescents in the United States is 6.06 per 100,000 according to the latest CBTRUS statistical report (1). High childhood cancerrelated mortality is observed in pediatric patients with CNS tumors, which is the second most malignancy after leukemia (2). Pediatric gliomas are the most common type therein, and the low-grade gliomas (WHO grades I and II) constitute a majority of pediatric gliomas, such as pilocytic astrocytoma and subependymal giant cell astrocytoma (3).…”
Section: Introductionmentioning
confidence: 99%
“…Brain tumors are the most common solid tumor in pediatrics, accounting for 23.7% of new cancer diagnoses in children ( 1 ), and the second most common pediatric malignancy after leukemia ( 2 , 3 ). The life-saving treatments these children receive may result in impaired brain structure and function, leading to long-term major cognitive deficits ( 1 , 4 8 ).…”
Section: Introductionmentioning
confidence: 99%